The National Football League and traumatic brain injury: blood-based evaluation at the game - Steven H Rauchman; Dimitris G Placantonakis; Allison B Reiss (Concussion, 2023)
Tweetable abstract #brain #injury in the #football #player - we need better #diagnosis and #prevention. #view our #latest #publication in the #journal Concussion @futuresciencegp on @thegame #Blood...